2019
DOI: 10.1111/adj.12690
|View full text |Cite
|
Sign up to set email alerts
|

Myofunctional therapy and prefabricated functional appliances: an overview of the history and evidence

Abstract: Malocclusion represents the clinically observable endpoint of numerous genetic and environmental influences. Oral Myofunctional Therapy (OMT) aims to treat malocclusions by improving the oral environment through re-education of musculature and respiratory patterns. Although the concept of OMT has existed since the early part of the 20th Century, many of its purported benefits for the treatment of malocclusion remain undemonstrated in the scientific literature. However, a more recent application of OMT for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
37
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 60 publications
2
37
0
5
Order By: Relevance
“…A recent systematic review, however, indicated that there is a lack of high-quality evidence in the existing literature regarding early orthodontic management and orofacial muscle training protocols on the correction of myofunctional and myoskeletal problems in the developing dentition (Koletsi et al, 2018). It is also important to note that Rogers considered myofunctional exercises as an aid in treatment and retention (Proffit and Mason, 1975) and not as a universal therapeutic approach for all orthodontic problems (Wishney et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review, however, indicated that there is a lack of high-quality evidence in the existing literature regarding early orthodontic management and orofacial muscle training protocols on the correction of myofunctional and myoskeletal problems in the developing dentition (Koletsi et al, 2018). It is also important to note that Rogers considered myofunctional exercises as an aid in treatment and retention (Proffit and Mason, 1975) and not as a universal therapeutic approach for all orthodontic problems (Wishney et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…T he use of orofacial myofunctional therapy (OMT) in orthodontic treatment dates back to the early to mid-1900s (Farrell & Darcy, 2018). Since this time, OMT has demonstrated improvements in orofacial function, including mandibular growth, malfunctions of the tongue, abnormal swallowing, nasal breathing, and facial appearance (Camacho et al, 2015;Wishney et al, 2019). Both Farrell and Darcy (2018) and Wishney et al (2019), in their reviews, discuss the establishment of OMT over 100 years ago by Alfred Rogers, who was a student of the influential orthodontist Edward Angle in the early 1900s.…”
mentioning
confidence: 99%
“…Since this time, OMT has demonstrated improvements in orofacial function, including mandibular growth, malfunctions of the tongue, abnormal swallowing, nasal breathing, and facial appearance (Camacho et al, 2015;Wishney et al, 2019). Both Farrell and Darcy (2018) and Wishney et al (2019), in their reviews, discuss the establishment of OMT over 100 years ago by Alfred Rogers, who was a student of the influential orthodontist Edward Angle in the early 1900s. It was Angle who suggested that there was a myofunctional origin to dental malocclusions and that restoration of the muscles would lead to normal orofacial function (Farrell & Darcy, 2018;Wishney et al, 2019).…”
mentioning
confidence: 99%
See 2 more Smart Citations